Peran Media Sosial Sebagai Alat Komunikasi Pemasaran Berbasis Online Dalam Meningkatkan Penjualan Di Pasar Bersehati Kota Manado - Riani Senduk; Yudith Rondonuwu; Hartati Umar; Imaculata Lamonge; Michiko Londok; Diana Wangania (Universitas 17 Agustus 1945 Semarang, 2024)
Online sales in Manado reflect the large number of Manadonese people who are interested in shopping online rather than going shopping in person to fulfill their needs and desires. The focus of the problem and aim of this research is to explain the role of social media as an online marketing communication tool in increasing sales of Pasar Bersehati. This research uses a qualitative approach which is a type of field research, by analyzing online buying and selling practices carried out by Bersehati Market Traders. Data collection techniques in this research were observation, interviews, literature study and documentation. The results of this research show that the communication process carried out by market traders with one heart in marketing their products via Instagram social media is by implementing a communication strategy that includes communication components (source, message, media, recipient, effect and feedback), as well as applying the 4P (product) marketing principles. , price, place, promotion). In marketing communications, there are also supporting and inhibiting factors. The supporting factor is the various social media features which are very helpful in marketing. The inhibiting factor is the existence of other online business competitors who are increasingly interested. The effectiveness of marketing communications carried out by market traders with one heart has a big influence as seen by the increasing level of sales.